A TEKNIK BIBLIOTHERAPY PADA KONSELI/SISWA BERKARAKTER INTROVERT: Jurnal Bimbingan dan Konseling (STKIP NU Kabupaten Tegal, 2021)
Bibliotherapy is one of the techniques used by counselors in carrying out a service activity in guidance and counseling by providing assistance using approaches or guides or library materials. The counselor compiles a list of books that help in changing the thoughts, feelings and behavior of the reader or client. Bibliotherapy here intends to assist clients in solving a problem and influencing the lives of clients by helping clients find pleasure in reading and escape from mental distress and the client's inability to express a problem with the counselor. With the aim of the client being able to find and be able to identify himself or the problems he has faced which the client himself is not able to convey to the counselor openly by releasing emotions, achieving new directions in his life and exploring new ways of interacting. One of the goals of counseling is to improve the client's ability to manage stress and anxiety.